Hybrid multistage framework for data manipulation by combining cryptography and steganography - Omnia Mohammed Osman; Mohammed Eltayeb Ahmed Kanona; Mohamed Khalafalla Hassan; Afra Adil Elsir Elkhair; Khalid Sheikhidris Mohamed (Institute of Advanced Engineering and Science, 2022)
In today's rapidly growing communication and internet technologies, such as 5G, cloud computing, and blockchain, information security has become a critical component. When data is transmitted in its raw form, it is vulnerable to a variety of cybersecurity assaults. In this hybrid multi-stage data encryption architecture, which builds sequential and pseudo-random encoding/decoding algorithms with pre-stage text encryption discovered that image resolution and attributes were unaffected by the change in image size after testing several text sizes with the cover image and various image formats, it is suitable that the text size should be 15% smaller than the cover image. Furthermore, when compared to sequential encoding/decoding, the hybrid cryptography and steganography-pseudo-random encoding/decoding procedure is more efficient and time consuming.